Kebangkrutan Perusahaan Menggunakan Model Altman dan Zavgren pada Perusahaan Food And Beverages - Agustina, Yeni; Rahmawati, Rahmawati (Bina Nusantara University, 2010)
The purpose of this research is to show the illustration of the financial performance in food and beverages companies during the years 2001, 2002, 2003, 2004, and 2005. Since the Indonesian economic crisis which began in middle 1997, most of industry sectors, including food and beverages companies, had some constraints in producing and actualizing their products. One of the important things in making decisions for company managers, creditors, and the future investors is the bankruptcy analysis model to predict company’s bankruptcy. This research used two models developed by Edward I. Altman (Model Z-Score) and Christine V. Zavgren (Logit Model). The result of this research is, generally, the financial conditions of the food and beverages companies are in bad conditions. This situation is connected with the low profitability, liquidity, and activity rates of those companies.